2017
DOI: 10.1051/matecconf/20179701027
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing High Performance Self Compacting Concrete

Abstract: Abstract. This paper's objectives are to learn the effect of glass powder, silica fume, Polycarboxylate Ether, and gravel to optimizing composition of each factor in making High Performance SCC. Taguchi method is proposed in this paper as best solution to minimize specimen variable which is more than 80 variations. Taguchi data analysis method is applied to provide composition, optimizing, and the effect of contributing materials for nine variable of specimens. Concrete's workability was analyzed using Slump f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…The two mixtures were less than the limit (<5 cm). This permeability shows the compactness of concrete due to the combination of silica fume and glass powder reducing porosity of concrete which prevents the infiltration of water [38]. There was a difference of 20% between MIX-SF and MIX.…”
Section: Notementioning
confidence: 95%
See 1 more Smart Citation
“…The two mixtures were less than the limit (<5 cm). This permeability shows the compactness of concrete due to the combination of silica fume and glass powder reducing porosity of concrete which prevents the infiltration of water [38]. There was a difference of 20% between MIX-SF and MIX.…”
Section: Notementioning
confidence: 95%
“…The slump loss result after one hour had insignificant decrease. Adding the glass powder improved the slump due to the low water absorption than silica fume which increased the the density of fresh mortar [12], [38]. The results indicated that VHPC had good workability.…”
Section: Notementioning
confidence: 95%